The Crystal Structure of the Spodoptera litura Chemosensory Protein CSP8 - Qian Jia; Hui Zeng; Jinbing Zhang; Shangfang Gao; Nan Xiao; Jing Tang; Xiaolin Dong; Wei Xie (Insects, 2021)
Spodoptera litura F. is a generalist herbivore and one of the most important economic pests feeding on about 300 host plants in many Asian countries. Specific insect behaviors can be stimulated after recognizing chemicals in the external environment through conserved chemosensory proteins (CSPs) in chemoreceptive organs, which are critical components of the olfactory systems. To explore its structural basis for ligand-recognizing capability, we solved the 2.3 Å crystal structure of the apoprotein of S. litura CSP8 (SlCSP8). The SlCSP8 protein displays a conserved spherical shape with a negatively charged surface. Our binding assays showed that SlCSP8 bound several candidate ligands with differential affinities, with rhodojaponin III being the most tightly bound ligand. Our crystallographic and biochemical studies provide important insight into the molecular recognition mechanism of the sensory protein SlCSP8 and the CSP family in general, and they suggest that CSP8 is critical for insects to identify rhodojaponin III, which may aid in the CSP-based rational drug design in the future.